2022
DOI: 10.1097/shk.0000000000001989
|View full text |Cite
|
Sign up to set email alerts
|

Mild Traumatic Brain Injury Attenuates Pneumonia-Induced Lung Injury by Modulations of Alveolar Macrophage Bactericidal Activity and M1 Polarization

Abstract: Traumatic brain injury is one of the main causes of death and disability worldwide, and results in multisystem complications. However, the mechanism of mild traumatic brain injury (MTBI) on lung injury remains unclear. In this study, we used a murine model of MTBI and pneumonia (Pseudomonas aeruginosa;) to explore the relationship between these conditions and the underlying mechanism. Methods: Mice (n = 104) were divided into control, MTBI, pneumonia, and MTBI + pneumonia groups. MTBI was induced by the weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
(57 reference statements)
0
3
0
Order By: Relevance
“…With an increasing awareness of brainlung interactions and the potential for an altered immune response as a consequence of brain injury [as reviewed elsewhere; e.g., 70], we had hypothesized that TBI alone may influence lung immune responses. For example, in models of lung infections with Pseudomonas aeruginosa, some studies have observed reduced bacterial clearance in animals that had previously sustained a TBI [32], while others have seen a reduced bacterial burden (presumably increased bacterial clearance) in TBI mice post-infection [71][72][73]. However, this was not the case in our model.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…With an increasing awareness of brainlung interactions and the potential for an altered immune response as a consequence of brain injury [as reviewed elsewhere; e.g., 70], we had hypothesized that TBI alone may influence lung immune responses. For example, in models of lung infections with Pseudomonas aeruginosa, some studies have observed reduced bacterial clearance in animals that had previously sustained a TBI [32], while others have seen a reduced bacterial burden (presumably increased bacterial clearance) in TBI mice post-infection [71][72][73]. However, this was not the case in our model.…”
Section: Discussionmentioning
confidence: 53%
“…While experimental paradigms of combined TBI and live infection models are rare, studies incorporating post-TBI infection with Citrobacter rodentium, Pseudomonas aeruginosa, or Streptococcus pneumoniae have all reported that the dual insult worsens neuroinflammation and mortality [32,33,38]. Of note, these studies all incorporated a moderate or severe TBI model, whereas other studies have suggested that mild TBI may conversely be protective against P. aeruginosa pneumonia [71,72]. A more complete understanding of combined neurotrauma and infection insults is necessary to ensure that model systems can generate data of clinical relevance [31].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have recently shown that brain injury can induce changes within systemic organs systems, including both the kidney and lung, both regions involved in regulating the HCO3, pH, and PaO2 of the blood. Kidney and lung pathology has been shown to occur in rodent models of mild TBI [ 69 , 70 , 71 , 72 , 73 ]. Retrospective clinical studies also found that either acute kidney injury [ 74 ] or acute lung injury [ 75 ] were associated with worse outcomes in TBI patients, indicating that systemic organ changes could be occurring in the human population as well.…”
Section: Discussionmentioning
confidence: 99%